Gamification of Wordwall Maze Chase as a STEM-Based Learning Media to Improve Students' Creative Thinking Skills (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
This study aims to determine the influence of Wordwall Maze Chase gamification as a STEM-based digital learning medium on improving students' creative thinking skills. This research uses a quantitative type of research. The study subjects were grade 5 elementary school students; as many as 31 respondents were selected with purposive sampling techniques. The data collection instrument uses an online questionnaire via a google forms link. The Pearson's correlation test showed that STEM-based Wordwall Maze Chase gamification learning media affected students' creative thinking skills by 0.926, which means it has a perfect correlation. Based on research in the field, using Wordwall Maze Chase gamification media has problems with cellphone performance and student screen resolution; the smaller the screen, the smaller the display of images and writing is also tiny. Learning using STEM-based Wordwall Maze Chase gamification media can be implemented in science, language, social science, and mathematics learning materials.